Divide f(x) by d(x), and write a summary statement in the form indicated.

f(x) = x^4 + 4x^3 + 6x^2 + 4x + 5: d(x) = x^2+1


•f(x)=(x^2+1)(x^2+4x+5)+12x-15

•f(x)=(x^2+1)(x^2+4x+5)

•f(x)=(x^2+1)(x^2-4x+5)

•f(x)=(x^2+1)(x^2-4x+5)+12x-15

Respuesta :

Answer:

The correct option is B)  [tex]f(x) =(x^2+1)(x^2+4x+5)[/tex]

Step-by-step explanation:

Consider the provided function.

[tex]f(x) = x^4 + 4x^3 + 6x^2 + 4x + 5[/tex] and [tex]d(x) = x^2+1[/tex]

We need to divide f(x) by d(x)

As we know: Dividend = Divisor × Quotient + Remainder

In the above function f(x) is dividend and divisor is d(x)

Divide the leading term of the dividend by the leading term of the divisor:[tex]\frac{x^4}{x^2}=x^2[/tex]

Write the calculated result in upper part of the table.

Multiply it by the divisor: [tex]x^2(x^2+1)=x^4+x^2[/tex]

Now Subtract the dividend from the obtained result:

[tex](x^4 + 4x^3 + 6x^2 + 4x + 5)-(x^4-x^2)=4x^3+5x^2+4x+5[/tex]

Again divide the leading term of the obtained remainder by the leading term of the divisor: [tex]\frac{4x^3}{x^2}=4x[/tex]

Write the calculated result in upper part of the table.

Multiply it by the divisor: [tex]4x(x^2+1)=4x^3+4x[/tex]

Subtract the dividend:

[tex](4x^3+5x^2+4x+5)-(4x^3+4x)=5x^2+5[/tex]

Divide the leading term of the obtained remainder by the leading term of the divisor: [tex]\frac{5x^2}{x^2}=5[/tex]

Multiply it by the divisor: [tex]5(x^2+1)=5x^2+5[/tex]

Subtract the dividend:

[tex](5x^2+5)-(5x^2+5)=0[/tex]

Therefore,

Dividend = [tex]x^4 + 4x^3 + 6x^2 + 4x + 5[/tex]

Divisor = [tex]x^2+1[/tex]

Quotient = [tex]x^2+4x+5[/tex]

Remainder = 0

Dividend = Divisor × Quotient + Remainder

[tex]f(x) = (x^2+1)(x^2+4x+5)[/tex]

Hence, the correct option is B)  [tex]f(x) =(x^2+1)(x^2+4x+5)[/tex]

Ver imagen FelisFelis
ACCESS MORE